2019
DOI: 10.1111/pbr.12699
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of improving forage maize starch degradability in European elite maize germplasm

Abstract: Improving maize starch content is of great importance for both forage and grain yield.In this study, 13 starch degradability traits were analysed including percentage of the seedling area, floury endosperm, hard endosperm of total grain area, percentage of the floury endosperm surface and vitreousness ratio surface hard: floury endosperm surface, etc. We mapped quantitative trait loci (QTL) in a biparental population of 309 doubled haploid lines based on field phenotyping at two locations. A genetic linkage ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The results obtained showed that within all analyzed groups of inbreds, there was a quantitative variability of grain quality traits. Its main reason should be to recognize the effects of polygenic complexes, which cause an independent effect on these characters (Guttierrez-Rojas et al, 2010;Yang et al, 2010;Li et al, 2018;Leng et al, 2019) and can modify phenotypic manifestation of mutant genes O2 and SU2, as well as the effect of their non-allelic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained showed that within all analyzed groups of inbreds, there was a quantitative variability of grain quality traits. Its main reason should be to recognize the effects of polygenic complexes, which cause an independent effect on these characters (Guttierrez-Rojas et al, 2010;Yang et al, 2010;Li et al, 2018;Leng et al, 2019) and can modify phenotypic manifestation of mutant genes O2 and SU2, as well as the effect of their non-allelic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…López-Malvar et al (2019) identified SNPs significantly associated with low stem hydroxycinnamate, which explained a low percentage of total phenotypic variability (7%-10%) but indirect selection based on cell wall kinases (WAKs) and members of the receptor-like cytoplasmic kinase (RLCK), acting as cell wall modulators, proved to be potential candidate genes for cell wall-bound hydroxycinnamate accumulation (Lopez-Malvar et al, 2019) (Table 2). Leng et al (2019) mapped seven (seedling fraction) to nine (vitreousness) QTLs for starch degradability traits in a DH population. These QTLs were distributed across all 10 chromosomes, except for chromosome 6, and explained phenotypic variance between 38.2% and 76.5%.…”
Section: Qtls and Genes Identified For Silage Traitsmentioning
confidence: 99%